Variations in the length of Scots pine (Pinus sylvestris L.) needles under the influence of climatic factors and solar activity in different conditions of northern taiga - Olga N. Tyukavina; Nikolay A. Neverov; Alexander L. Mineev (Journal of Forest Science, 2019)
The aim of the study was to assess the influence of climatic factors on the growth of pine needles in different conditions of the water regime of soil. Studies were conducted in lichen pine forests, cowberry pine forests, blueberry pine forests, shrub-sphagnum pine forest and pine on swamp in the Arkhangelsk forestry regions (northern taiga). The needle length is influenced by solar activity (the Wolf number). The effect of solar activity on increasing the needle length is greatest in optimal growing conditions. In northern taiga conditions, air temperature is the main climatic factor affecting the growth of needles. In the blueberry, cowberry and lichen pine forests, an inverse high correlation of the needle length with the night air temperature of August of the current year was revealed. The pine on swamp revealed a high correlation between the needle length and the air temperature at the end of July of the current year of needle development. In the year preceding the needle development, a high inverse correlation was found between the needle length and the temperature of mid-September in the cowberry and blueberry pine forests. In the current year, high correlations of the lengths of needles and precipitation were observed in extreme growing conditions.